2019
DOI: 10.1111/bdi.12876
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated hippocampal biological aging in bipolar disorder

Abstract: Objectives Evidence suggests accelerated aging mechanisms in bipolar disorder (BD), including DNA methylation (DNAm) aging in blood. However, it is unknown whether such mechanisms are also evident in the brain, in particular in association with other biological clocks. To investigate this, we interrogated genome‐wide DNAm in postmortem hippocampus from 32 BD‐I patients and 32 non‐psychiatric controls group‐matched for age and sex from the NIMH Human Brain Collection Core. Methods DNAm age and epigenetic aging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 88 publications
(113 reference statements)
5
23
1
Order By: Relevance
“… 83 - 85 More recently, a marker of biological aging based solely on DNA methylation levels (“epigenetic age” or “DNA methylation age”) 86 has been used to explore the aging processes in BD, and the results suggest accelerated epigenetic aging in the blood and brain of BD patients compared to controls. 71 , 87 Recent evidence that the epigenetic clock can be pharmacologically reversed in humans 88 offers an interesting treatment possibility for the modulation of premature aging in BD.…”
Section: Genetics and Epigenetics Of Bipolar Disordermentioning
confidence: 99%
“… 83 - 85 More recently, a marker of biological aging based solely on DNA methylation levels (“epigenetic age” or “DNA methylation age”) 86 has been used to explore the aging processes in BD, and the results suggest accelerated epigenetic aging in the blood and brain of BD patients compared to controls. 71 , 87 Recent evidence that the epigenetic clock can be pharmacologically reversed in humans 88 offers an interesting treatment possibility for the modulation of premature aging in BD.…”
Section: Genetics and Epigenetics Of Bipolar Disordermentioning
confidence: 99%
“…In BD, several candidate-gene-based approaches have been performed, such as BDNF, COMT , and SLC6A4 genes in postmortem brains 12 . Additionally, comprehensive DNA methylation studies have revealed expression-linked DNA methylation changes in the cerebellum 14 , accelerated aging in the hippocampus 15 , loss of brain laterality associated with TGFB2 methylation 16 , and methylation imbalance of synaptic function-related genes between the frontal and temporal cortices 17 . However, there have been no established findings that were replicated in multiple studies.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found altered mtDNAcn in BD patients compared to controls. Significantly lower mtDNAcn have been observed in BD leukocytes (Chang et al, 2014;Yamaki et al, 2018;Wang et al, 2020), postmortem hippocampus (Fries et al, 2019), and left frontopolar cortex (Tsujii et al, 2019). Chung et al (2020) reported lower mtDNAcn in BDI patients compared to higher mtDNAcn in BDII patients compared to controls.…”
Section: Mitochondrial Dna Copy Number In Bipolar Disordermentioning
confidence: 89%